"Forgetting familiar faces": Staff perceptions of dementia in people with intellectual disabilities. (29th May 2018) - Ryan, Christian; MacHale, Rosemary; Hickey, Emma
Abstract : Accessible summary: Dementia is an illness of the brain. It can make people forgetful and confused. We talked to staff about what it is like to support people with dementia. They told us that working with dementia is upsetting for family, friends and staff. Abstract: Background: Living with dementia is challenging, but poses unique difficulties for people with an intellectual disability. The process of dementia is also challenging for family, carers and friends. Materials and Methods: This study explores the impact of dementia on direct care staff using a focus group methodology. Thematic analysis was used to investigate the staff narratives. Results: Four key themes that emerged were as follows: (a) the difficulty of recognising symptoms of dementia in people with intellectual disabilities, (b) the process of diagnosis, (c) the challenge of dementia for the person, (d) the emotional impact of dementia for other people. Conclusion: The themes identify a number of important potential targets for supporting staff and peers in this challenging area of work.